Didactic problems of using distance lectures in the study of clinical anatomy and operative surgery in higher medical education institutions - Kobzar , O.B.; Shevchenko , O.O. (Морфологія / Morphologia / Morfologìâ, 2025)
The article presents the results of a study on the didactic problems of using distance lectures in the study of clinical anatomy and operative surgery. An attempt has been made to analyze modern trends in addressing these issues in the context of distance learning. Objective. The study aims to identify didactic problems associated with the use of distance lectures in clinical anatomy and operative surgery, evaluate the advantages, and weigh the disadvantages of the lecture method in both distance and blended learning formats. Methods. The study is based on an analysis of the experience of delivering distance lectures from 2020 to 2025 at Bogomolets National Medical University in the disciplines of clinical anatomy and operative surgery. These lectures were conducted for 2nd- to 4th-year students of the medical, pediatric, and dental faculties, as well as for surgical specialty interns. Results and conclusion. It was found that distance lectures provide flexibility and accessibility in education, foster independence and responsibility for one’s own learning, provided that interactive methods, modern technologies, and consistent feedback are utilized. Conducting distance lectures requires instructors to adapt educational materials to the specifics of the online format, structure content clearly, develop skills for live-streaming lectures, and maintain real-time interaction with students. The study presents practical ways to improve lecturing skills to enhance the effectiveness of distance lectures. The factors that reduce the efficiency and quality of distance lectures in higher medical education are also outlined.